Alternatively spliced mu opioid receptor C termini impact the diverse actions of morphine - Xu, Jin (J Clin Invest, 2017)
Extensive 3′ alternative splicing of the mu opioid receptor gene OPRM1 creates multiple C-terminal splice variants. However, their behavioral relevance remains unknown. The present study generated 3 mutant mouse models with truncated C termini in 2 different mouse strains, C57BL/6J (B6) and 129/SvEv (129). One mouse truncated all C termini downstream of Oprm1 exon 3 (mE3M mice), while the other two selectively truncated C-terminal tails encoded by either exon 4 (mE4M mice) or exon 7 (mE7M mice). Studies of these mice revealed divergent roles for the C termini in morphine-induced behaviors, highlighting the importance of C-terminal variants in complex morphine actions. In mE7M-B6 mice, the exon 7–associated truncation diminished morphine tolerance and reward without altering physical dependence, whereas the exon 4–associated truncation in mE4M-B6 mice facilitated morphine tolerance and reduced morphine dependence without affecting morphine reward. mE7M-B6 mutant mice lost morphine-induced receptor desensitization in the brain stem and hypothalamus, consistent with exon 7 involvement in morphine tolerance. In cell-based studies, exon 7–associated variants shifted the bias of several mu opioids toward β-arrestin 2 over G protein activation compared with the exon 4–associated variant, suggesting an interaction of exon 7–associated C-terminal tails with β-arrestin 2 in morphine-induced desensitization and tolerance. Together, the differential effects of C-terminal truncation illustrate the pharmacological importance of OPRM1 3′ alternative splicing.